Genetic Divergence in Chickpea (Cicer arietinum L.) (Bangladesh Journal of Agricultural Research, 2012)
Genetic diversity of 27 chickpea genotypes was studied through Mahalanobis D2 and Principal Component analysis. The genotypes under study fall into five clusters. The cluster II contained the highest number of genotypes (11) and Cluster I contained the lowest. Cluster I produced the highest mean value for number of pods per plant. The inter cluster distances were much higher than the intra cluster distances. Cluster V exhibited the highest intra cluster distance while the lowest distance was observed in cluster I. The highest inter cluster distance was observed between cluster I and II while the lowest was between cluster III and V. Considering all the characters, it was suggested that the genotypes BD6549, BD6603, and BD6548 could used as parents for future breeding programs to develop high yielding varieties of chickpea. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11184 Bangladesh J. Agril. Res. 37(1): 129-136, March 2012